Importance Performance Analysis (IPA) Halal Attributes (Studi pada Hotel Shafirah Syariah dan Al-Madinah Kota Pariaman) - Safitri, Tania Permatalia; Abrian, Youmil (Lembaga Yasin AlSys, 2023)
The general objective of this research was to determine the level of importance and need for halal attributes in Kota Pariaman hotels. This type of research is quantitative research using descriptive methods. This research was conducted on halal attributes with the IPA method at the Shafira Syariah hotel and the Al-Madinah hotel, Pariaman City. The time of this research was March - April 2023. Based on the description and results of the level of importance and halal requirements for the attributes of the Shafira and Al-Madinah hotels, Pariaman City, using the IPA (Importance Performance Analysis) method which has been stated above, it can be concluded in general, as many 52% of guests stated that the halal attribute was very important at the Shafrira Syariah and Al-Madinah Hotels, Pariaman City.